PERAN PEMERINTAH DALAM PEMBERDAYAAN EKONOMI DENGAN MENINGKATKAN MUTU KOPERASI PASCA PANDEMI COVID-19 - Sinaga, Lenni (Tinta Nusantara 2018 Vol.1, 2023)
The aim of this research is: To improve the quality of cooperatives in Indonesia through the government for the sake of economic empowerment. The design used in this research is a qualitative descriptive analysis method, which involves analysis, description and summary of various conditions obtained from interviews or direct observation in the field of data collection on the problem being studied. With quality values that have been determined in accordance with the required standards, so it is hoped that it can be implemented well. The role of the community, including students, also provides an important contribution. The government needs to form regional units to be able to optimally increase its role in cooperatives. People who really understand technology, especially students, can take part in it.